The sexuality of the elderly in the nursing consultation context: a phenomenological analysis of luso-brazilians - Saraiva, Renata (2018)
Intoduction: Listening to elderly people in Brazil and Portugal, it was intended to promote reflective discussions that shared experiences and experiences, in order to interact with the cultural plurality existing between the two countries to help the understanding of the sexuality of the elderly, and of the possible behavioral changes acquired after actions implemented in a learning situation. Objectives: Describe, understand and discuss the interrelation between nurses and clients in the educational action on the sexuality of the elderly in the context of the nursing consultation. Method: Outcome thesis on the sexuality of the elderly in the context of the nursing consultation, translated into a systematic review. The relevance was to listen to elderly and nurses in Brazil and Portugal, with the intention of promoting reflective discussions that shared experiences and experiences of interaction with the existing cultural plurality. 41 elderly people and 26 nurses participated. Scenarios used were HESFA - Brazil and IPG - Portugal, in accordance with the ethical criteria, National Health Council, resolution 466/12. Results: They were presented as concrete categories of the lived, which revealed the "reasons-why" of the elderly and the nurses. Conclusion: Therefore, the absence of intention demonstrates the need to discuss the subject in theory since graduation and, in the practical field, in nursing consultations.